Treatment of cerebellar ataxia. (October 2014) - Jones, Tracy M; Shaw, Jessica D; Sullivan, Kelly; Zesiewicz, Theresa A
SUMMARY : Symptoms of cerebellar degeneration include ataxia or wide-based gait, visual and speech dysfunction, dysmetria, and dyscoordination. The etiology of cerebellar degeneration is vast and often complex, and requires neuroimaging, lab assessments, and a thorough family history to delineate its cause. There is currently no accepted treatment of hereditary cerebellar degeneration, although several pharmaceutical agents have shown potential promise.